From Theater to Novel. Inflections of the Homosexual Voice in Manuel Puig’s Kiss of the Spider Woman - Canala, Juan Pablo (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article aims to study the writing process of Manuel Puig’s novel Kiss of the Spider Woman (1976) from his Mexican exile perspective. The archival turn and gender studies are implemented here in order to reflect on the construction of the homosexual voice in the novel from the traces in the author’s papers. We are interested in analyzing the way in which Puig —during his joint work with lesbian activist Nancy Cárdenas— appropriates both the play The Boys in the Band by Mart Crowley, and some theoretical sources from the homosexual militancy groups of the 1970s. This work reveals the way in which these productions influenced both the dialogic technique and the construction of the homosexual voice.